2010
DOI: 10.1002/jsfa.4046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermentation by lactic acid bacteria on the antigenicity of bovine whey proteins

Abstract: The fermentation with lactic acid bacteria is an effective way to reduce whey proteins antigenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 23 publications
7
78
0
2
Order By: Relevance
“…Classic immunoglobulin-E (IgE)-mediated food allergies are classified as type-I immediate hypersensitivity reaction and around 1-2 % of adults and up to 5-7 % of children suffer from some type of food allergy with foods (Mills and Breiteneder 2005). Furthermore, food hypersensitivity seems to be on the rise and has become a major public health concern around the world in recent years (Bu et al 2010;Sathe and Sharma 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Classic immunoglobulin-E (IgE)-mediated food allergies are classified as type-I immediate hypersensitivity reaction and around 1-2 % of adults and up to 5-7 % of children suffer from some type of food allergy with foods (Mills and Breiteneder 2005). Furthermore, food hypersensitivity seems to be on the rise and has become a major public health concern around the world in recent years (Bu et al 2010;Sathe and Sharma 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Proteases cleave milk proteins into peptides and may therefore have important effects on the further gastro-intestinal milk digestibility, release of the bioactive peptides, and hydrolysis of antigenic epitopes with the consequent decrease of milk allergenicity (Kleber, Weirich, & Hinrichs, 2006). Recently, Bu, Luo, Zhang, and Chen (2010) have shown that the use of combined strains of Lactobacillus helveticus and Streptococcus thermophilus has a synergic effect on reduction of the antigenicity of whey proteins when grown in skim milk. In previous studies, we showed that other thermophilic LAB strains were able to hydrolyse pure BLG using a non-proliferating cell system (Pescuma, Hébert, Mozzi, & Font de Valdez, 2007;Pescuma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…bulgaricus CRL 656 degraded BLG during their growth in whey protein concentrate (WPC 35%) (Pescuma, Hébert, Mozzi, & Font de Valdez, 2010). Several reports have shown that milk or whey fermentation by LAB could reduce protein allergenicity (Kleber et al, 2006;Bu, Luo, Zhang, & Chen, 2010). However, no studies were carried out using free BLG, avoiding the interference of other proteins or sugars from the food matrix, which can affect the BLG allergenic properties (Davis & Williams, 1998;Svenning, Brynhildsvold, Molland, Langsrud, & Vegarud, 2000;Ehn, Ekstrand, Bengtsson, & Ahlstedt, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that combination of two LAB strains (Lb. helveticus and S. thermophilus) leads to the reduction of antigenicity of both whey proteins (α-lactoalbunim and β-lactoglobulin) during fermentation (Bu et al, 2010). Pescuma et al (2011) found out decreasing of β-lactoblobulin antigenicity during fermentation by Lb.…”
Section: Reduction Of Allergenicity By Lactic Acid Bacteriamentioning
confidence: 94%
“…The reduction of milk protein antigenicity depends on the species of LAB and on condition of fermentation. Bu et al (2010) chose three LAB strains for fermentation of milk (Lb. bulgaricus, S. thermophilus and Lb.…”
Section: Reduction Of Allergenicity By Lactic Acid Bacteriamentioning
confidence: 99%